The use of humanure for cereal production under conventional and regenerative farming models - findings from a three-year grassland-to-arable transition - Katie Allen; Effie Papargyropoulou; Ruth Wade; Barbara Evans (PLoS ONE, 2026)
Humanure (human excrement recycled for agricultural use) offers a low-cost, simple treatment option for dry sanitation systems, and a promising organic amendment for crop production. However, no long-term studies have evaluated its impacts under different land management approaches. This study presents findings from a three-year field trial (2021–2024) in West Yorkshire, UK, assessing the effects of humanure on cereal crop yield and soil properties under conventional and regenerative farming practices of a former grassland. The experiment used a semi-randomised block design with two management regimes (conventional and regenerative) and three fertilisation treatments (control, synthetic fertiliser, and humanure), each replicated three times. Crop results showed that humanure increased crop yields compared to the control, demonstrating a fertilisation effect, which was more pronounced under regenerative management. However, yields from humanure treatments were lower than those from synthetic fertilisers. Regenerative management produced higher yields than conventional across all fertiliser types. Soil analyses revealed that fertiliser type had limited influence on physical soil properties, but regenerative practices significantly improved water-stable aggregates. Soil organic matter and total carbon were higher under humanure than other fertiliser regimes, and higher under regenerative management across all fertilisers. Humanure elevated phosphorus and potassium levels, but not outside of acceptable limits. Biological indicators, including worm counts, soil respiration, and fungal biomass, were slightly elevated under humanure treatments and consistently higher in regenerative systems. Due to small sample sizes, detailed statistical analysis was not appropriate, and instead trends are observed and discussed. Overall, this study suggests that humanure is a promising soil amendment, especially when combined with regenerative land management. More investigation is warranted, with greater replication to enable statistical analysis, in order to further explore of the role humanure in realising a circular economy for sanitation and sustainable agriculture.